Klass, kön och Shakespeare: Elise Karlssons Smuts - Sivefors, Per (Tidskrift för litteraturvetenskap, 2024)
Class, gender and Shakespeare. Elise Karlsson's Smuts This essay suggests that the use of Shakespeare in Elise Karlsson’s novel Smuts (2021) serves to accentuate and develop the novel’s thematic focus on work, precarity, class, and gender. Revolving around a production of A Midsummer Night’s Dream at a fictitious theatre in Stockholm, Smuts aligns itself with tendencies in Karlsson’s previous work as well as in contemporary Swedish literature: as an assistant script editor, its narrator is a freelance worker in an economy where work is precarious and perceived—despite the supposedly high status of her work in the cultural sector—as badly paid and, literally, meaningless. Shakespeare’s play becomes a focal point for these themes not just because of the extensive character parallels with Smuts, but also because the complex notions of class, work and female subjugation in Karlsson’s novel can be seen as developments of themes that are very much present in the play. In other words, Smuts is a good example of contemporary ‘working-class literature’ in Sweden, and as the essay suggests, it builds up its focus on precarity, class, and gender by means of intertextual parallelisms with Shakespeare.